Focal Intestinal Lipogranulomatous Lymphangitis in 6 Dogs (2008–2011). (7th November 2013) - Watson, V.E.; Hobday, M.M.; Durham, A.C.
<x xml:space="preserve">Abstract</x> Background Lipogranulomatous lymphangitis is inflammation of the intestinal lymphatic vessels and surrounding tissues caused by chronic leakage of lipid‐laden chyle. Grossly, lipogranulomas are typically disseminated small masses on the serosa and surrounding lymphatic vessels and consist of epithelioid macrophages, multinucleated giant cells, and cholesterol. Lipogranulomatous lymphangitis is occasionally seen in patients with lymphangiectasia and protein‐losing enteropathy (PLE). Objectives To characterize the historical features, clinical signs, treatment, histopathology, and outcome of dogs with focal lipogranulomatous lymphangitis. Animals Six dogs with ultrasonographic evidence of focal, regional small intestinal masses, often with involvement of the adjacent mesentery, and a diagnosis of focal lipogranulomatous lymphangitis based on histopathology of biopsied masses. Results The median age of dogs was 6.9 years (range 3–10 years). All dogs had total protein, globulin, and albumin concentrations within the reference range at initial presentation and had intestinal masses identified on abdominal ultrasound examination. Histopathologic evaluation of lesions identified severe mural and mesenteric lipogranulomatous lymphangitis. Lymphangiectasia was noted in 5 cases and only in sections within the mass‐like lesion; tissue without lipogranulomas had minimal lymphangiectasia, suggesting a localized phenomenon. Postoperative outcomes ranged from remission of clinical signs with no subsequent treatment for 10–12 months in 2 dogs, postoperative management with medical and nutritional management in 3 dogs, and no outcome for 1 case. Conclusions and Clinical Importance This case series describes a unique mass‐like manifestation of intestinal lipogranulomatous lymphangitis and should be considered as a possible differential diagnosis in dogs with an intestinal mass.